Pengaruh Bahan Baku, Tenaga Kerja dan Investasi Terhadap Produksi Serta Ekspor Keramik Di Kabupaten Tabanan - Istanti, Yeni; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 2, Februari 2016 (pp. 216 - 315), 2016)
Ceramics Bali Province is one of the top ten commodities handicrafts penetrate the export market. Export of ceramics fluctuate due to factors of production. Tabanan regency as the largest contributor to the export of ceramics has production factors such as the value of raw materials, manpower, and the high investment but does not offset the high production values. This study uses panel data comprising nine cross section ceramic companies in Tabanan and time series data 2008-2014 period. This study uses data collection and in-depth structured interviews, as well as non-behavioral observation. The analysis technique used is path analysis. Based on the analysis found that the Raw Materials, Labor, Investment positive effect on production. Labor and Production positive effect on exports. Investments no significant effect on exports. Production is mediating variables in the indirect influence of Raw Materials. The next production is not mediating variables in the influence of labor and investment towards export.
Keywords: bahan baku, tenaga kerja, investasi, produksi, ekspor